(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Consumption of arsenic contaminated water has been associated with diverse health defects such as cancer and skin lesions. Some plants of medicinal value have been reported to show protective effects against toxins. In this study, the effects of ethanol extract of the leaves of Irvingia gabonensis (IG) against sodium arsenite (SA) induced hepatotoxicity and clastogenicity in male Wistar rats was investigated. Eight groups of five rats each were used for the study. They were administered with 250 or 500 mg/kg body weight of IG with or without SA at 2.5 mg/kg body weight. IG extract has a significant (p<0.05) reducing effect on serum liver function enzymes, aspartate aminotransferase (AST), alanine aminotransferase (ALT), and gamma glutamyltransferase (γGT) activities. This was corroborated with the histopathological analysis findings. Also the groups treated with both the extract and SA recorded significantly (p<0.05) reduced number of micronuclei when compared with the group treated with SA only. IG extract also reduced the oxidative stress induced by SA as measured by the reduced generation of hydrogen peroxide (H2O2) and significant (p<0.05) difference in the CAT and SOD activities between the groups treated with both SA and extract, and the positive control group administered SA alone. This study therefore shows that the ethanol leaf extract of Irvingia gabonensis have hepatoprotective and anticlastogenic effects against sodium arsenite-induced toxicity possibly by enhancing the antioxidant status in the Wistar rats.